2016
DOI: 10.1089/hs.2016.0054
|View full text |Cite
|
Sign up to set email alerts
|

Refugees of the Syrian Civil War: Impact on Reemerging Infections, Health Services, and Biosecurity in Turkey

Abstract: After the Arab Spring uprising, Syria descended into a civil war in 2011. By March 2016, the United Nations reported that 13.5 million Syrians required humanitarian assistance, including 6.6 million internally displaced persons and more than 4.8 million refugees outside of Syria. Turkey is currently hosting the largest number of Syrian refugees-more than 2.7 million. A limited number of refugees are living in camps settled around the border, and others are spread throughout Turkey. This explosive and unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 26 publications
2
70
1
1
Order By: Relevance
“…The notification rates by age group in the Syrian refugee population indicate that the seroprevalence of Syrian children and young adults might be lower than described in the literature and seroprevalence data for these age groups are needed. High incidence of HA among Syrian refugees has also been reported from Turkey [17], while a HA outbreak among Syrian refugees in northern Iraq has been documented [18]. Moreover, most children have asymptomatic HAV infection; thus, the number of infections that occurred during the study period was probably much higher than reported.…”
Section: Discussionmentioning
confidence: 84%
“…The notification rates by age group in the Syrian refugee population indicate that the seroprevalence of Syrian children and young adults might be lower than described in the literature and seroprevalence data for these age groups are needed. High incidence of HA among Syrian refugees has also been reported from Turkey [17], while a HA outbreak among Syrian refugees in northern Iraq has been documented [18]. Moreover, most children have asymptomatic HAV infection; thus, the number of infections that occurred during the study period was probably much higher than reported.…”
Section: Discussionmentioning
confidence: 84%
“…As reemerging infections measles, poliomyelitis, leishmaniasis, and multidrug-resistant tuberculosis were most frequently seen in Syrian refugees [13] . Multidrug-resistant gram-negative bacterial infections were seen with high incidence in gunshot or surgical wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Turkey has been affected from illegal animal and human movements. In particular, regional conflicts in the countries neighboring Turkey has led to massive refugee and illegal human movements during the past 30 years (15)(16)(17). In addition, Turkey has highly variable climatic conditions, vegetation structures, wildlife, and particularly many sanctuaries for immigrant birds.…”
Section: Introductionmentioning
confidence: 99%